Enhanced microencapsulation of C-phycocyanin from Arthrospira by freeze-drying with different wall materials - Pan-utai, Wanida (Array, 2021)
Research background. C-phycocyanin (C-PC), a water-soluble blue pigment, was extracted from microalgae Arthrospira sp. C-PC could be a good substitute for synthetic pigments with high antioxidant activity. However, C-PC is unstable due to sensitivity to temperature, light, pH and oxygen; therefore, applications of C-PC in food and other products are limited. Microencapsulation of C-PC using freeze-drying is a solution to this problem and is considered a suitable method for drying the heat-sensitive pigment. Experimental approach. C-phycocyanin was extracted from Arthrospira platensis. C-PC microcapsules were modified by freeze-drying, with maltodextrin and gum Arabic used as microencapsulation wall materials at different fractions from 0 to 100 %. The physical properties including moisture content and water activity, solubility, hygroscopicity, bulk density, colour appearance, particle morphology and size distribution of the produced powders were evaluated. Thermal stability and antioxidant activity of freeze-dried microencapsulated C-PC powders were also assessed. Results and conclusions. Freeze-dried microencapsulated C-PC powders with maltodextrin and gum Arabic as wall materials gave high encapsulation efficiency of around 99 %. At higher gum Arabic mass fraction, moisture content decreased and water activity improved. Maltodextrin gave higher solubility of C-PC powders whereas gum Arabic led to a similar colour of C-PC to those without microencapsulation. Freeze dried microencapsulated C-PC powders were composed of different sized microparticles regardless of the combination of wall materials with amorphous glassy shapes. Thermal stability of encapsulated C-PC increased and also showed high antioxidant properties. Novelty and scientific contribution. This study demonstrates that the freeze-dried microencapsulated C-PC powders have pigment stability with antioxidant properties and are resistant to high temperatures.